Prognosic Factors Related to The Complete Hematologic Response (CHR) in 3 Months in Leukemia Granulositic Patients Administered with Imatinib Mesylate - Rinaldi, Ikhwan; Reksodiputro, Arry H. (UI Scholars Hub, 2020)
Introduction. The complete hematologic response is an integral part to achieve the complete cytogenetic response target and the major molecular response of imatinib mesylate therapy, although it does not determine the prognosis. The complete hematologic response in Indonesia is lower than in the world (74% vs. 95%). Sixty percent of chronic myeloid leukemia patients in Indonesia were administered hydroxyurea before imatinib mesylate. Chronic myeloid leukaemia (CML) patients in Indonesia are younger than in other countries. This study aimed to determine what prognostic factors which affect the complete hematological response of chronic phase CML patients who received imatinib mesylate in Indonesia. Methods. The study was done by retrospective cohort design using the medical records data of chronic myeloid leukemia patients who were treated at Teratai Clinic and hematology clinic RSCM and received imatinib mesylate therapy from January 2004-December 2011. Results. Most of the study subjects were male (61.5%), aged 26-40 years (47.4%), duration of diagnosis <12 months>(69.2%), duration of hydroxyurea therapy <6 months>(64.1%), hemoglobin concentration <12 g>/dl (69.2%), leukocyte count ≥50,000 (48.7%), platelet count 0 – <450,000 (42.3%), spleen size ≥10 cm (55.1%), low Sokal score (42.3%), and achieve a complete hematologic response within 3 months (57.7%). Duration of hydroxyurea therapy <6 months is prognostic factor higher CHR achievement. Conclusions. Clinical and laboratory characteristics CML patients in Indonesia are different than CML patients in the world. Duration of diagnosis until imatinib mesylate administration <12 months, duration of hydroxyurea administration <6 months, and hemoglobin concentration ≤12 g/dl were associated with the achievement of complete hematological response of chronic CML patients in Indonesia. Duration of hydroxyurea administration <6 months was identified as independent factor of achievement of complete hematological response of chronic CML patients in Indonesia.